Comparison between the modeled and simulation of the Flickermeter based on the Standard IEC-61000-4-15 through the Discrete Wavelet Transform and Fast Fourier Transform - El Montoya, Dan (Revista Técnica da Faculdade de Engenharia da de Zulia)
Voltage fluctuation is the first cause of the flicker light effect. Some definitions and standards have been proposed to measure the grade of the flicker. The standards define admissible flicker levels in function of the frequency. Algorithms based on the Fast Fourier Transform have been used a lot in digital analysis of flicker voltage. In the last decade it has been implemented the wavelet transform in many issues on power electric systems. The applications have been focused on the classification of the disturbances in measurement on power quality. The wavelet analysis has been used on steady state signal analysis. In this way the wavelet transform has been used to identify harmonics, sub harmonics and no-integer harmonics. Also the Morlet and the Gaussian wavelets have been used in the calculation of the flicker signal spectrum. This will be crucial to calculate or Pst of the standard IEC-41000-6-15. The objective of this paper is to calculate short-term flicker evaluation through the Discrete Wavelet Transform and the Fast Fourier Transform in order to compare results.